Pengetahuan Akseptor Tentang Kontrasepsi IUD - Eka Nur Rahayu; Marinda Anggasari; Siti Abdillah (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2020)
Background: Family Planning (KB) is a program in Indonesia that aims to reduce birth rates inIndonesia. The choice of contraceptive behavior can be influenced by several factors includingeducation, parity, knowledge and environment. Research Objectives to determine the relationshipof education and parity with knowledge of IUD family planning in family planning acceptors.Methods: This study used an analytical survey method and a cross sectional approach wasconducted in January-March in the hamlet of Dronco, Girirejo, Imogiri, Bantul. The number ofsamples is 164 people, accidental sampling techniques. The research instruments used in thisstudy were questionnaires and data analysis using Kendall's know.Results: the results of the study found that the highest education acceptors were secondaryeducation with a percentage of 51.2%. The parity of acceptors namely acceptors has 2 childrenwith a percentage of 45.7%. The most used contraception is injection with a percentage of 57.9%.There is a relationship between education and parity with knowledge of IUD contraception infamily planning acceptors in Dronco hamlet.Keywords: Education, Parity, IUD contraceptive knowledge